Discourses of childhood and Young people in Psychosocial devices in Chile: La mirada de los interventores psicosociales - Araya Vera, Marina Alejandra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study explored the discourses and their subjectivation processes carried out by psychosocial interveners of childhood and adolescence who participate in Chilean State devices. Based on qualitative methodology, semi-structured interviews and critical discourse analysis. The results show meanings of childhood and adolescence associated with care, danger and a subject of rights with agency. The latter resists institutional violence through mutual support among peers and with interveners. This research underlines the importance of participatory psychosocial interventions with children and adolescents as social and political agents.